Calculations of power take-off element length values during shape changes caused by weather - Капітанчук, К. І.; Андріїшин, М. П. (Science-based technologies, 2018)
Use of sea wave’s energy is the extremely necessary. Scientific development for creation of wave energy stations, are extraordinarily actual. Wave energy station is able effectively to work at any size of waves, because form of energetically absorbing element is self-regulated under the action of waves. Problem of destructive influence of waves during sharp change of force of a wind and as consequence of amplitude of fluctuations of a surface of the sea, it is solved by flooding is a energetically absorbing element and a platform of station on depth, where fluctuations of waves correspond to calculation values, without change of an operating mode of the station. Thus consumers stably receive the declared quantity of the electric power. In article for the first time calculations of power take-off element length dependencies of wave length during WEC submersion and algorithms of such calculations are presented. Changes of length in power take-off element on working surface are in belt form are accounted for.